Passthrough Extended Reality in Maritime Commissioning - Rajamäki, Joni; Tapola, Mirva; Salonen, Mikko; Heimo, Olli; Lehtonen, Teijo (United States, 2026)
In this paper a feasibility study of passthrough Extended Reality (XR) with maritime commissioning as a use case is presented. Passthrough XR is a technology designed to implement Augmented Reality (AR) with modern Virtual Reality (VR) devices. The driving force for this research arises from the shipbuilding industry's need to optimise installation and validation processes during critical phases, such as sea trials and larger commissioning process. Prior research into the employment of XR technologies within the shipbuilding industry shows that tools allowing hands-free operation should be favoured, and the use of video passthrough HMDs should be avoided due to the (then) limited capabilities offered by the technology. The research involved the development of an XR environment designed for analysing the passthrough capabilities of modern VR HMDs using the Meta Quest 3 platform. The primary objective of this case study was to assess the maturity of contemporary mobile XR technologies for industrial applications within the shipbuilding sector via a testing session held for participants linked to the shipbuilding industry (n=33). The results revealed potential for the contemporary application of passthrough XR technologies in shipbuilding.
Human-Computer Interaction & Emerging Technologies : Proceedings of the 16th International Conference on Applied Human Factors and Ergonomics and the Affiliated Conferences, Orlando, Florida, USA 26-30 July 2025